The Effect of Out-of-School Learning Activities on Gifted Students’ Affective and Behavioral Tendencies Towards The Environment - Yakup Ayaydin; Burçin Acar Şeşen; Sezen Camci Erdoğan; Duygu Ün; Hakan Özçiriş (Journal of Science Learning, 2023)
This study investigates the effect of out-of-school activities on gifted students' affective and behavioral tendencies. Mixed method research with a single group pre and post-test experimental design was used in this study. Twenty-five gifted students from Turkey-İstanbul participated in this study. “Environmental Affect Scale” and “Environmental Behavior Scale” were used, and semi-structured interviews were conducted. Results showed that out-of-school activities positively affected the students’ affective and behavioral tendencies toward the environment. It was also found that the awareness of students on environmental problems increased, and they began to produce their solutions to these problems.